2016
DOI: 10.1016/j.devcel.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine RNA Modification Regulates Shoot Stem Cell Fate in Arabidopsis

Abstract: N(6)-Methyladenosine (m(6)A) represents the most prevalent internal modification on mRNA and requires a multicomponent m(6)A methyltransferase complex in mammals. How their plant counterparts determine the global m(6)A modification landscape and its molecular link to plant development remain unknown. Here we show that FKBP12 INTERACTING PROTEIN 37 KD (FIP37) is a core component of the m(6)A methyltransferase complex, which underlies control of shoot stem cell fate in Arabidopsis. The mutants lacking FIP37 exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
513
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 316 publications
(552 citation statements)
references
References 54 publications
(89 reference statements)
37
513
0
2
Order By: Relevance
“…However, we identified a viable hypomorphic allele of FIP37 , caused by a T‐DNA insertion within its 7 th intron ( fip37‐4 , identical to that described in Shen et al . (2016); Fig. 4a).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…However, we identified a viable hypomorphic allele of FIP37 , caused by a T‐DNA insertion within its 7 th intron ( fip37‐4 , identical to that described in Shen et al . (2016); Fig. 4a).…”
Section: Resultsmentioning
confidence: 87%
“…We have circumvented this embryo lethality by establishing a collection of hypomorphic, mutants or RNAi lines for each of the proteins associated with the m 6 A writer complex in order to study the effects of reduced m 6 A in postembryonic development. In a recently published study, (Shen et al ., 2016) reported that reduced FIP37 expression resulted in increased proliferation of the shoot apical meristem. Our findings independently expand this, further revealing that impaired expression of any of the five m 6 A writer components we identify results in a range of developmental defects, including vascular formation, implying a role for m 6 A in establishing and maintaining these processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies revealed m 6 A modulation of mRNA expression to be involved in obesity [19], the circadian clock [20], and the DNA damage response [21]. Additionally, it also plays important roles in a variety of biological processes including pluripotency maintenance of stem cells [22][23][24], the maternal-to-zygotic transition [25], sex determination [26,27] and plant shoot stem cell fate determination [28]. As the key 'writer' of m 6 A modification, Mettl3 has been demonstrated to modulate neuronal functions and sex determination in Drosophila and regulate early embryonic development and stem cell pluripotency in mice [22-24, 26, 27].…”
Section: Introductionmentioning
confidence: 99%